Development and Preliminary Testing of the Health in Community Survey - Iezzoni, Lisa I; Barreto, Esteban A; Wint, Amy J; Hong, Clemens S. K; Donelan, Karen (Journal of health care for the poor and underserved, 2015)
Objectives . Develop and pilot test the Health in Community Survey (HCS), to collect patients’ perceptions of care integration between traditional care providers and community-based services that address social determinants of health. Research design . Interviews of working-age, English-or Spanish-speaking patients with multiple chronic conditions to identify survey domains; cognitive interviews and pilot test of HCS Version 1. Results . Preliminary interview subjects identified diverse care concerns. From these findings, we designed six HCS domains. Cognitive interviews identified problems relating to patients’ perceptions about limited function and disability. Nearly one-third of pilot test subjects reported they did not definitely have enough resources for food, transportation, doctor and hospital bills, and medications; 41.6% said their clinicians only sometimes or never knew about their resource problems. Conclusions . Although it requires further validation, the HCS offers insights into patients’ perceptions of care integration between traditional health care providers and services addressing social determinants of health.